Interactions Between Two Invertebrate Pathogens: An Endophytic Fungus and an Externally Applied Bacterium - Wakil, Waqas; Tahir, Muhammad; Al-Sadi, Abdullah M.; Shapiro-Ilan, David (Frontiers in Microbiology, 2020)
The members of family Noctuidae exist in diverse environments and many species from this group are of agriculture importance, particularly Helicoverpa spp. Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) is a major pest of many legumes and cereal crops. Due to environmental and regulatory concerns, safe alternatives to broad spectrum chemical insecticides are needed for the control of key noctuid pests such as H. armigera. A strain of Beauveria bassiana s.l. (Cordycipitaceae: Hypocreales) was evaluated for its ability to colonize endophytically in chickpea plants, and its effectiveness against L2 and L4 instars of H. armigera. B. bassiana was inoculated to chickpea plants through injection and endophytic establishment was confirmed by re-isolating the fungi from leaf samples. A detached leaf assay was used to evaluate pathogenicity. Bacillus thuringiensis was also applied to both larval stages through leaf dip method. In a novel approach, combined treatments of bacteria and endophytic fungi were compared with single-pathogen treatments. Relative to the single treatments, the combined pathogen treatments exhibited an increase in larval mortality, and decrease in pupation, adult emergence and egg eclosion. Specifically, synergistic effects on mortality were observed when larvae were exposed to simultaneous application of B. bassiana (1×108 conidia ml-1) with B. thuringiensis (0.75 µg g-1). Both instars exhibited varying level of growth, development, frass production, diet consumption and fecundity when exposed to the chickpea leaves inoculated with endophytic B. bassiana and dipped with sub-lethal doses of B. thuringiensis. These findings indicate that the integrated application of endophytic colonized B. bassiana and B. thuringiensis can be effectively used against H. armigera.